Combinatorial Cytotoxic Effects of Gelam Honey and 5-Fluorouracil against Human Adenocarcinoma Colon Cancer HT-29 Cells In Vitro - Syed Ahmad Tajudin T-Johari; Fatimah Hashim; Wan Iryani Ismail; Abdul Manaf Ali (International Journal of Cell Biology)
Combination of natural products with chemodrugs is becoming a trend in discovering new therapeutics approach for enhancing the cancer treatment process. In the present study, we aimed to investigate the cytotoxic and apoptosis induction of Gelam honey (GH) combined with or without 5-Fluorouracil (5-FU) on HT-29 cells. The cell viability was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay to assess cytotoxicity. Morphological changes and apoptosis were determined by the inverted microscope, Annexin V-FITC, and DNA fragmentation via flow cytometric analysis, respectively. Our results demonstrate that combined treatment revealed a remarkable and concentration-dependent cytotoxic effect on HT-29 cells in comparison with GH and 5-FU alone. Flow cytometry analysis showed that early apoptosis event was more pronounced in combined treatment. In addition, compared to 5-FU alone, apoptosis of HT-29 cells treated with combinations of GH and 5-FU demonstrated increasing percentages of fragmented DNA. Our results suggest that GH has a synergistic cytotoxic effect with 5-FU in HT-29 cell lines in vitro. Although the actions of the molecular mechanisms are not yet clear, the results reveal that the combination of GH and 5-FU could have the potential as a therapeutic agent.